A review on revolutionary technique for phosphate removal in wastewater using green coagulant. (April 2023) - Owodunni, Amina A.; Ismail, Suzylawati; Kurniawan, Setyo Budi; Ahmad, Azmi; Imron, Muhammad Fauzul; Abdullah, Siti Rozaimah Sheikh
Abstract: Phosphorus is one of the pollutant's parameters causing environmental pollution, known as eutrophication. Coagulation-flocculation is a widely known technology to treat phosphorus-containing wastewater; however, using metal-based coagulants raises some environmental concerns related to their toxicity. Natural coagulants offer an option to treat wastewater containing phosphorus with comparable performance to chemical coagulants. The utilization of natural coagulants removed phosphorus (as phosphate) from wastewater with an efficiency of up to 99.6 %. Removal of phosphate from wastewater by natural coagulant was highly correlated with the charge neutralization mechanism. The use of phosphate-rich resultant sludge as soil conditioner/fertilizer is made possible by using natural coagulant compared to metal-based coagulant due to its lower metal content and toxicity to plants and aquatic organisms. The combination of treatment with other technologies, such as the filtration unit, showed significant improvement in phosphorus removal, which also alleviated the load of the next unit, including ultraviolet disinfection, whose performance might be affected by high solid content. Despite its promising performance, the selection of raw materials, extraction, and purification of natural coagulants become the major challenge in the further application of this option. This review article discusses the aforementioned topics and highlights future research directions of developing simpler extraction/purification processes of natural coagulants and analysis of natural coagulants' performance in treating different speciation of phosphorus in wastewater to enhance this particular knowledge. Graphical abstract: Unlabelled Image Highlights: Literature review on phosphate removal by coagulants is limited. Knowledge gaps in phosphate removal by natural coagulants were outlined. The use of natural coagulants to treat phosphate-rich wastewater was investigated. Natural coagulants achieved good performance in phosphorus removal. Mechanism involved in phosphate removal was proposed.